INTERNATIONAL TAXATION AND CAPITALISM a heterodox economics perspective. - Blanco, Andrés (ROUTLEDGE, 2025)
The book introduces a novel approach to international taxation through the lens of heterodox economic and social theories, in particular Marxism. The book argues that the radical reorganization of the international tax system that has been underway for the last few decades - initiated by the OECD, and furthered by the G20 and the European Union - is a response to changes in the global structure of capitalism, especially in terms of center-periphery. Through both normative analysis and empirical evidence, the book shows that the global tax system emerging from these changes consolidates the regulatory and tax revenue control of the central states. It also demonstrates that this consolidation and centralisation is designed to enable the dominance of multinational corporations in the global economy. This path of international taxation is explained in the book through certain general concepts of Marxian economic theory, such as the accumulation of capital and the tendency of the rate of profit to fall, along with other specific developments, such as the unequal participation of the different regions of the world in the capitalist system and a general theory of money that incorporates elements proposed by some sectors of post-Keynesianism. This book is invaluable reading for anyone interested in global capitalism, the financial system, heterodox economics, and Marxist theory.
Keywords: Taxation -- Law and legislation.; Capitalism.; elektronické knihy; electronic books